Analisis Pengalaman Kerja, Semangat Kerja dan Promosi Jabatan Terhadap Kinerja Karyawan pada PT. PepperLunch Medan - Yona Lamtiurna Lase; Eli Delvi Yanti (BADAN PENERBIT STIEPARI PRESS, 2025)
This research was conducted at PT. Pepperlunc Medan with the aim of determining the influence of work experience, work enthusiasm and job promotion on employee performance. The population is 41 employees working in the company and the sampling is done with saturated samples so that the number of samples is 41 respondents. The type of data used in this study is primary data, while the data source comes from secondary data. Data collection techniques are carried out through literature studies, surveys, and direct observation. The data analysis methods used include multiple linear regression, classical assumption testing, and hypothesis testing. The findings show that work experience, work enthusiasm, and job promotion have a positive and significant effect on employee performance, both separately and simultaneously. There is a sufficient correlation between work experience, work enthusiasm and job promotion with performance, while the contribution of the influence of the variables studied is 30.4%, while the remaining 69.6% comes from other factors outside the research variables.